Tratamento e aproveitamento de resíduos da produção do biodiesel: água residuária e glicerol - Zenatti, Dilcemara Cristina (2011)
Nowadays, much has been said about global warming and its possible causes, but the scientific consensus identifies increased levels of greenhouse gases produced by human activity as the main influence. One alternative to reduce emissions of greenhouse gases is to replace fossil fuels with renewable sources such as biodiesel. The process of biodiesel production is composed of the following steps: preparation of raw material, the transesterification reaction, phase separation, recovery and dehydration of alcohol, glycerine distillation and purification of this renewable fuel, with the byproduct glycerin and water as waste purification. Since, for each 100 liters of biodiesel, 10 kg of crude glycerin are produced, generating on average 60 liters of wastewater. Therefore, studying alternatives to the use of glycerin and economically viable treatment of wastewater has become an important aspect of this production chain. In order to meet these assumptions, this thesis is structured in two chapters. In Chapter 1, we tackle the treatment of wastewater from biodiesel production system in dissolved air flotation (DAF), which was tested in two coagulants (aluminum sulfate and ferric chloride) and two auxiliary of flocculation (polifloc and tanfloc). The experiment was conducted at the Laboratory of Environmental Sanitation of the State University of Paraná, using a Jar Test adapted for testing of flotation. The combination showed better efficiency in the clarification of the effluent to remove color and turbidity and also better efficiency in removing oil and grease and COD was combined with aluminum sulfate polifloc synthetic polymer at pH 6 and recirculation rates of 15%. In Chapter 2 we studied the production of methane in anaerobic co-digestion of glycerin and swine wastewater. During the process tested the increment in biogas production and methane with increasing initial organic load, performed by the addition of glycerol as substrate. The experiment was conducted at the Technical University of Lisbon/ Institute of Agronomy, in a complete mix anaerobic reactor of laboratory scale. The addition of glycerol in the ratio of 3% v / v proved effective in increasing the production of methane.